Serological detection of Grapevine leafroll-associated virus 4 in grapevine growing areas of India using polyclonal antiserum raised against the recombinant coat protein. (July 2018) - Rai, Richa; Khurana, S.M.Paul; Kumar, Sandeep; Gupta, Nitika; Baranwal, V.K.
Abstract: Grapevine leafroll disease (GLD), caused by a complex of serologically and genetically distinct or related viral species termed as Grapevine leafroll associated viruses (GLRaVs), is a serious threat to the grape production worldwide. Recently, Grapevine leafroll-associated virus 4 (GLRaV-4) has been reported in the Indian vineyards, mostly as a mixed infection with GLRaV-3 and GLRaV-1. In order to screen the planting material, a polyclonal antiserum against the in vitro expressed coat protein (CP) of GLRaV-4 was produced. The antiserum, purified IgGs and conjugated IgGs detected GLRaV-4 in crude saps of infected grapevines and purified coat protein when used in antigen coated plate enzyme-linked immunosorbent assay (ACP-ELISA), double antibody sandwich enzyme-linked immunosorbent assay (DAS-ELISA), Western blotting and dot immunobinding assay (DIBA). GLRaV-4 could be detected in 54% (39 out of 72) of symptomatic grapevine samples from different grape growing regions of India using DAS-ELISA. The validation of DAS-ELISA results was done by RT-PCR using GLRaV-4 CP-specific primers. To the best of our knowledge, this is the first report of a polyclonal antiserum against the in vitro expressed CP of GLRaV-4 and its successful application in diagnosis of the virus in grape vineyards of India. Highlights: The widespread occurrence of GLRaV-4 was detected which was upto 54% (39 out of 72) in the grapevine samples collected from Indian vineyards. The immuno reagents raised against in vitro expressed CP, successfully detected antigens in both non denaturing (ELISA) and denaturing (western blot) procedures. Immunodiagnostic developed in present study will help in large scale screening or indexing of grapevine propagating materials to produce GLRaV-4 free grapevines.